The Role of QRIS in the Perspective of Islamic Economics: A Case Study of Photocopying Around the Banyumas Campus - Alen, Winci (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
The development of digital technology has driven transformation in various aspects of life, including payment systems. One of the innovations developed in Indonesia is the Quick Response Code Indonesian Standard (QRIS), which has been widely adopted in various sectors, including small and medium enterprises. This study aims to analyze the role of QRIS from the perspective of Islamic economics with a case study of a photocopying business around the Banyumas campus. The method used is qualitative with a case study approach, where data is collected through observation, interviews with photocopying business owners and students as the main users, and literature studies related to Islamic economics. The results of the study indicate that the implementation of QRIS in photocopying provides various benefits, such as ease of transactions, operational efficiency, and increased convenience for students. However, there are several challenges in implementing QRIS, especially related to transaction fee deductions that potentially contain usury elements and delays in disbursing funds to recipient accounts. From a Sharia economic perspective, although the use of QRIS, in general, does not conflict with Sharia principles, aspects of contracts, transparency, and fairness in transaction costs need to be studied further to comply with the principles of Islamic muamalah. This study recommends education for business actors and students regarding Sharia financial literacy in digital systems and the development of QRIS mechanisms that are more on Islamic economic principles. In addition, further research related to QRIS regulations and policies in the Sharia economic system is needed to ensure that this digital payment system can fully support Sharia-based financial inclusion.